The importance of bismuth-containing quadruple therapy in Helicobacter pylori eradication in an era of increasing antibiotic resistance - Yi HU; Yuan ZHUANG; Nong-Hua LYU (Yixue xinzhi zazhi)
Approximately half of the global population is infected with Helicobacter pylori (Hp). Currently, the main challenge in the field of Hp is that the antibiotic resistance of Hp is increased, leading to the decreased efficacy of regimens. The prevalence of Hp primary resistance to clarithromycin, metronidazole, and levofloxacin is above the alarming level in most areas of the world. Moreover, Hp was defined as a high-priority bacterium in the World Health Organization (WHO) priority list of antibiotic-resistant bacteria. Bismuth has several advantages, including low resistance rate, safe and improving the eradication rate in Hp resistant strains. Therefore, bismuth-containing quadruple therapy is recommended as the first-line regimens by the international Hp consensus report. This article emphasizes the importance of bismuth-containing quadruple therapy in Hp eradication in an era of increasing antibiotic resistance through reviewing the recently published Hp consensus report and relevant clinical articles.